Колекція ґрунтопокривних троянд у Національному дендропарку «Софіївка» НАНУ - Мороз, О.К.; Дениско, І.Л.; Банк, В.С. (Автохтонні та інтродуковані рослини, 2010)
Наведено дані досліджень перспективності застосування ґрунтопокривних троянд в озелененні. Изучали возможность интродукции почвопокровных роз в Национальном дендропарке «Софиевка». Розы данной группы хорошо адаптируются в условиях Правобережной Лесостепи Украины. Самый эффективный способ размножения почвопокровных роз — черенкование. Укоренение происходит в течение 4–6 дней и достигает 100 %. Благодаря широкому диапазону возможностей использования и неприхотливости почвопокровные розы могут быть успешно использованы в озеленении населенных пунктов. The capacity for introduction of ground-cover roses in the National Dendrological Park “Sofiyivka» was researched. The roses of this garden group establish well in the conditions of the Right-bank forest-steppe zone of Ukraine (Zone 5). Propagation by cuttings is the most effective propagation method for groundcover roses. They form roots within 4–5 days. The rooting can reach 100 %. Thanks to the wide range of utilization capacity and to their unpretentiousness the ground-cover roses can be applied successfully for landscape design in settlements.